Changes in the rates and population structure of methicillin-resistant Staphylococcus aureus (MRSA) from bloodstream infections: A single-centre experience (2000–2015). (June 2019) - Nikolaras, Georgios P.; Papaparaskevas, Joseph; Samarkos, Michael; Tzouvelekis, Leonidas S.; Psychogiou, Mina; Pavlopoulou, Ioanna; Goukos, Demetrios; Polonyfi, Katerina; Pantazatou, Aggeliki; Deliolanis, Ioannis; Smilakou, Stavroula; Daikos, George L.
Highlights: Rate of MRSA bloodstream infections is declining. The pandemic HA-MRSA clone ST239-III (CC8) has been eliminated. CA-MRSA ST80-IV causes bloodstream infections in hospitalised patients. There was an upward trend in the prevalence of HA-MRSA ST5-II (CC5). Abstract: Objectives: The aim of this study was to assess the rate of methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSIs) and the population structure of MRSA isolates recovered between 2000–2015 in a tertiary-care hospital in Athens, Greece. Methods: Non-duplicate MRSA blood isolates recovered during the study period were examined. Antimicrobial susceptibility testing was performed by Kirby–Bauer and gradient strip methods. Carriage of PVL and mecA genes was examined by PCR. Genetic relatedness of the isolates was studied by SCC mec, spa and multilocus sequence typing. Results: A total of 398 MRSA BSI cases were identified. A decreasing trend in incidence from 1.69/10 000 patient-days in 2000 to 1.39/10 000 patient-days in 2015 ( P  = 0.038) and in prevalence from 64.7% to 36.4% ( P  = 0.008), respectively, was observed, whereas the incidence of methicillin-susceptible S. aureus BSI increased. MRSA isolates exhibiting resistance to common antistaphylococcal agents (excluding glycopeptides and the newer antistaphylococcals) decreased from 84.8% in 2000 to 0% in 2011 and were progressively 'replaced' by more susceptible phenotypes. A strong association between antimicrobial resistance phenotype and molecular type was observed. The pandemic HA-MRSA clone ST239-III progressively declined in parallel with increasing isolation frequency of two clonal complexes (CCs): HA-MRSA CC5, with the majority of isolates belonging to ST5-II; and CA-MRSA CC80, represented mainly by ST80-IV-t044, PVL+. Conclusion: The decline in MRSA BSI rates observed in our institution was associated with changes in population structure of the organism. This decline may be related to biological properties of the prevailing MRSA clones.